2021
DOI: 10.48550/arxiv.2104.00778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short proofs of three results about intersecting systems

Abstract: In this note, we give short proofs of two theorems in extremal set theory. The first one is a determination of the maximum size of a nontrivial k-uniform, d-wise intersecting family for n ≥ 1 + d 2 (k − d + 2), which improves upon a recent result of O'Neill and Verstraëte. Our proof also extends to d-wise, t-intersecting families, and from this result we obtain a version of the Erdős-Ko-Rado theorem for d-wise, t-intersecting families.The second result partially proves a conjecture of Frankl and Tokushige abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Finally in the last section we discuss possible extensions to non-trivial r-wise intersecting families for r ≥ 4, and a related k-uniform problem. In particular we include counterexamples to recent conjectures posed by O'Neill and Versträete [15], and by Balogh and Linz [3].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally in the last section we discuss possible extensions to non-trivial r-wise intersecting families for r ≥ 4, and a related k-uniform problem. In particular we include counterexamples to recent conjectures posed by O'Neill and Versträete [15], and by Balogh and Linz [3].…”
Section: Introductionmentioning
confidence: 92%
“…Theorem 3 suggests that F 3 (n, k, 1) could be a counterexample to the conjecture if n and k are sufficiently large and roughly Balogh and Linz [3] made another conjecture. They constructed a family BL r (n, k) as possibly the largest non-trivial r-wise intersecting families in [n] k .…”
Section: Subcasementioning
confidence: 99%
See 1 more Smart Citation
“…A further study direction is to reduce the value of n 1 (k, d). Balogh and Linz [4], recently, gave a very short proof to greatly improve the lower bound for n in Corollary 1.6(1) by using the simple fact that every non-trivial d-wise intersecting family is (d − 1)intersecting. Since the largest non-trivial (d − 1)-intersecting families have been investigated systematically in [1,2,3] and they are exactly d-wise intersecting, as a simple corollary, Balogh and Linz showed that the largest non-trivial d-wise intersecting k-uniform family is isomorphic to one of H(k, d, 2) and H(k, d, k − d + 2) for any n > (1 + d 2 )(k − d + 2).…”
Section: Comparison Of the Sizes Of Extremal Familiesmentioning
confidence: 99%
“…Conjecture 4.6 would imply that it is the case when H = K t for all t ≥ 5. In 2012, the authors of [29] raised the question of whether the Erdős-Ko-Rado property holds whenever H is 2-connected, but a construction of Balogh and Linz [6] shows that when H = K s,t and t > 2 2s − 2s − 1, the Erdős-Ko-Rado property does not hold for the H-intersection problem, so even the condition of H being s-connected is insufficient to guarantee the Erdős-Ko-Rado property (for any s ∈ N).…”
Section: Imposing Extra Structure On the Ground Setmentioning
confidence: 99%